Routine citizen Internet practices and cyber victimization: a state-wide study in Virginia - Gainey, Randy R. (Criminal justice studies, 2023)
Cybercrime has become a major societal concern, and a better understanding OF cybercrime is needed to target and prevent it more effectively, minimize its consequences, and provide support for victims. Research on cybercrime victimization has exploded in the past few years, but much of it relies on convenience samples and is largely descriptive in nature. The research presented here involves the collection of data from a large sample of Virginia households in 2022 (n = 1,206). The data are analyzed to provide a partial test of routine activity theory to better understand fraud and theft via the Internet. The data provide a solid baseline for describing the extent of cyber victimization across the state. Bivariate and multivariate analyses (logistic regressions) show support for routine activity theory and provide important insights for future research. In particular, we find that certain routine Internet activities may better predict unique forms of cybervictimization than others and that length of time on the Internet is not a good indicator of exposure to motivated offenders. Further, protective guardianship mediates the effects of exposure to motivated offenders; thus, efforts to educate the public on best practices are needed. We conclude that to better assess cybercrime, victimization and engagement, better measurement and longitudinal panel data will be needed.